Standing up for a Sustainable World: Voices of Change - Claude Henry (Edward Elgar Publishing, 2020)
The world has witnessed extraordinary economic growth, poverty reduction and increased life expectancy and population since the end of WWII, but it has occurred at the expense of undermining life support systems on Earth and subjecting future generations to the real risk of destabilising the planet. This timely book exposes and explores this colossal environmental cost and the dangerous position the world is now in. Standing up for a Sustainable World is written by and about key individuals who have not only understood the threats to our planet, but also become witness to them and confronted them.